Perbandingan Efektivitas Larutan Daun Jeruk Purut (Citrus hystrix) Dan Daun Kemangi (Ocimum sanctum) Sebagai Larvasida Aedes spp - Rachma Nanytha; Muhammad Irfa'i; Isnawati Isnawati; Noraida Noraida (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Nowadays, the cases of dengue hemorrhagic fever are progressively increasing and necessitating control. One of the easiest controls in breaking the life cycle of Aedes spp. mosquitoes is to kill mosquito larvae using plants as natural larvacides are environmentally friendly. One of them is using purut lime leaves and basil leaves. The study aims to determine the effectiveness comparison of solution purut lime leaves and basil leaves toward Aedes spp. larvae mortality. This research method is a true experiment with a Post-Test Only Control Group design. It is also followed by concentration at control (0%), 1,5%, 2,5%, 3,5%, 4,5%, and 5,5% with 4 repetitions. The sample was 1.200 instar Aedes spp. III larvae. The results showed the effectiveness of the kaffir lime leaf solution was at the lowest concentration of 3.5% with the mortality of 18 Aedes spp. larvae and the effective concentration of basil leaves was 4.5% with 15 larvae mortality. From an economic and availability perspective, basil leaves are easier to find, making it easier to apply. This makes it easier to apply. Water reservoirs are difficult to clean outside the home.